Annotated key to Lambdin's introduction to Biblical Hebrew - Williamson, H. G. M. (Hugh Godfrey Maturin), 1947- (T & T Clark biblical languages., 2004)
Lambdin's Introduction to Biblical Hebrew has established itself as a standard textbook in colleges and universities as well as being frequently used by those who wish to teach themselves Biblical Hebrew. The lack of a key to the many exercises in the book has been widely regretted, but this lack is made good with the present publication. Having used Lambdin as a teaching aid for more than ten years, however, Williamson has become aware of some areas in which students still find difficulty. He has therefore supplemented his Key with many further comments and explanations drawn from his teachin.